Probiotic and Antimicrobial Potential of Enterococcus faecalis M26 Recovered from Healthy Vietnamese Newborns' Stool - Nguyen Ai Linh; Nguyen Khanh Linh; Nguyen Thanh Vu; Nguyen Phuong Thuy (Bogor Agricultural University, Indonesia, 2026)
The neonatal gut microbiota, seeded by pioneer bacteria from meconium, is fundamental to lifelong health. Meconium is an underexplored reservoir of host-adapted bacteria with probiotic potential, especially in underrepresented populations, such as those in Vietnam. This study aimed to isolate and characterise Lactic Acid Bacteria (LAB) from the meconium of healthy Vietnamese newborns to identify novel probiotic candidates. From 20 meconium samples, 30 presumptive LAB isolates were selected after phenotypic screening. These isolates underwent comprehensive in vitro assessment. We tested their tolerance to simulated gastrointestinal conditions (pH 2.0 and 0.4% bile salts) and antimicrobial activity against Escherichia coli, Salmonella enterica, and Staphylococcus aureus. Safety was evaluated through antibiotic susceptibility testing and PCR screening for virulence genes. Isolate M26 showed the highest resilience, maintaining a viability of 6.22±0.49 Log CFU/mL at pH 2.0 and 6.31±0.58 Log CFU/mL in 0.4% bile salts. The neutralised cell-free supernatant of M26 showed moderate, broad-spectrum antimicrobial activity against all pathogens tested. M26 was sensitive to clinically relevant antibiotics and lacked key virulence factors (esp, gelE, cylA) and antibiotic resistance genes (vanA, vanB). 16S rRNA gene sequencing identified M26 as Enterococcus faecalis. These findings suggest that neonatal meconium is a source of robust LAB. E. faecalis M26, with high gastrointestinal tolerance and a favourable safety profile, warrants further investigation as a potential region-specific probiotic.